2017
DOI: 10.1080/00036846.2017.1358446
|View full text |Cite
|
Sign up to set email alerts
|

Financial development, financial liberalization and social capital

Abstract: The relationship between financial liberalization policies and financial development is controversial. The impact of these policies differs greatly across countries. In the literature, the quality of formal institutions has been identified as an important source of this heterogeneity, as countries with a weak institutional environment generally fail to benefit from financial liberalization. Using panel data covering 82 countries for the period 1973-2008, we find evidence that social capital may substitute for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Productivity is also affected by the degree of financial development. This is aligned with the findings of Biljanovska and Sandri (2018) and Elkhuizen et al (2018). Based on a sample of 86 advanced and emerging countries, for instance, Biljanovska and Sandri (2018) demonstrated that structural reforms, including those of the banking sector, have positive effects on productivity growth.…”
Section: Literature Reviewsupporting
confidence: 82%
“…Productivity is also affected by the degree of financial development. This is aligned with the findings of Biljanovska and Sandri (2018) and Elkhuizen et al (2018). Based on a sample of 86 advanced and emerging countries, for instance, Biljanovska and Sandri (2018) demonstrated that structural reforms, including those of the banking sector, have positive effects on productivity growth.…”
Section: Literature Reviewsupporting
confidence: 82%
“…The coefficients of control variables (trade openness, inflation and size of population) are also reported in Table- (Rodrik, 1992) and increase vulnerability to international shocks (Yilmazkuday, 2011). Inflation and population size are negatively related with financial development because both these variables reduce efficiency of the finance sector (Ahmad 2013, Allen et al 2014, Mahawiya 2015, Elkhuizen et al 2017. The results of diagnostic tests indicate that both models are well specified.…”
Section: Empirical Results and Discussionmentioning
confidence: 96%
“…Finally, Stiglitz (2000) argued that capital inflows following financial globalization is of speculative nature and may not be a mode of long-term investment. The sudden outflow of capital may lead to bank runs and banking crises (Elkhuizen et al 2017).…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…An extensive literature points out that legal systems with better enforcement of property rights and protection of legal rights of investors promote financial development (see La Porta et al 1998Porta et al , 2000Beck and Levine, 2008;Kim and Lin 2011). Similarly, financial liberalisation is normally, although not necessarily (Elkhuizen et al 2018), correlated to financial development (Chinn and Ito 2006;Michael D. Bordo and Christopher Meissner 2012).…”
Section: Baltagi 2001mentioning
confidence: 99%